Analysis of Delayed Onset Muscle Soreness in the Gastrocnemius Muscle Post Pre-Competition Athlete for the 2024 POPDA Batam Basketball Team Athlete - Widodo, Widodo; Handayani, Widya; Manullang, Jujur Gunawan (PPSDP International Journal of Education, 2024)
The aim of this study is to analyze the delayed onset of muscle soreness in the Gatrocnemius muscle after the pre-competition for the 2024 POPDA Batam men’s and women’s basketball teams. This research is a descriptive study using a survey method. The sample for this study was 24 people consisting of 12 male athletes and 12 female athletes. The research instrument used was the results of Delayed Onset Muscle Sores (DOMS) measurements carried out after 48 hours of pre-exercise. The data analysis used is descriptive statistics. The results of the research were that those experiencing very severe pain were athletes presenting (0%) and female presentations (0%), conditions of severe pain for male presentations (66.6%) and female presentations (50%), moderate pain conditions for male presentations (25%) and presentation daughter (25%), mild pain condition of presentation son (8.3%) and presentation daughter (25%), non-pain condition of presentation son (0%) and presentation daughter (0%).